Representasi Budaya Patriarki dalam Film Gadis Kretek: Kajian Semiotika Roland Barthes - Farah Nazifa; Wardiana Wardiana; Lina Sundana; Razali Razali (Multiverse: Open Multidisciplinary Journal, 2026)
Patriarchal culture remains a significant social issue frequently represented in cinematic narratives, reflecting unequal gender relations and the marginalization of women within cultural and familial structures. This study aims to examine how patriarchal culture is represented in the 2023 film Gadis Kretek by addressing the question of how signs and meanings construct patriarchal ideology through Roland Barthes’ semiotic framework. The research employed a qualitative descriptive approach, with data collected through systematic observation, dialogue transcription, and scene documentation from the film. Data were analyzed using Barthes’ concepts of denotation, connotation, and myth to interpret the symbolic meanings embedded in characters, dialogues, and visual representations. The findings identified 11 significant representations of patriarchal culture that reveal the normalization of male dominance, gender-based power relations, restrictions on women's autonomy, and the perpetuation of traditional gender roles within family and social institutions. The study concludes that Gadis Kretek not only portrays patriarchal practices as cultural realities but also critically exposes the ideological mechanisms through which patriarchal values are reproduced and legitimized in society, highlighting the film's role as a medium for social reflection and cultural critique.